Productive group work : how to engage students, build teamwork, and promote understanding - Frey, Nancy, 1959-; Everlove, Sandi; Fisher, Douglas, 1965- (Alexandria, Va. : ASCD, 2009)
Provides strategies for effective group work in the classroom, discussing how to create interdependence and positive interactions, design challenging and engaging tasks, ensure accountability, foster interpersonal skills, assess learning, and other related topics; and includes examples.
Defining productive group work -- Using positive interdependence -- Promoting face-to-face interaction -- Ensuring individual and group accountability -- Building interpersonal and small-group skills -- Incorporating group processing -- Getting started: questions and answers.
Includes bibliographical references (p. 116-120) and index.
Teacher Librarian.
Teacher Librarian, April 2010.
Professional
Keywords: Active learning; Group work in education; Team learning approach in education; Cooperative learning; Learning and scholarship